(untitled) (Bangladesh Pharmaceutical Journal, 2012)
Hyperlipidemia is one of the major causes of disability in western as well as in developing countries. The present study was designed to investigate the effect of the ethanolic leaf extract of a Bangladeshi medicinal plant Acacia nilotica (AN) on adrenaline-induced hyperlipidemia and cardiac remodeling in rats. The plant extract and commercial lipid lowering drug atorvastatine were administered in adrenaline-induced hyperlipidemic rats (AIHRs) through intraperitoneal route for one week at a dose of 30 mg and 0.04 mg per 150 gm body weight of rat, respectively. The AN extract showed a significant (P<0.01) decrease in lipid profile, and reducing the left ventricular hypertrophy (heart weight/body weight), heart weight, cardiac myocytes size as well as kidney, pancreas and liver weight of AIHRs. The observation was also made for consecutive four weeks (long term treatment) to confirm the results obtained in one week model. The results indicated that the leaf extract of A. nilotica in comparison with atorvastatine has got profound hypolipidemic and anticardiac remodeling activities. DOI: http://dx.doi.org/10.3329/bpj.v15i2.12578 Bangladesh Pharmaceutical Journal 15(2): 135-139, 2012